Flame-retardant properties and mechanism of LGF/PBT/DOPO-HQ-conjugated flame-retardant composites - Sun, Junzhuo; Zhang, Daohai; Shang, Xiaoyu; Tan, Fang; Bao, Dongmei; Qin, Shuhao (Frontiers in Chemistry, 2022)
In this article, long fiber reinforced polybutylene terephthalate (LGF/PBT/DOPO-HQ) flame-retardant composites were prepared using 10-(2,5-dihydroxy phenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO-HQ) as the conjugated flame-retardant. The effects of different flame-retardant contents on the combustion properties of the composites were investigated. The results showed that after adding 14% of DOPO-HQ, the flame-retardant effect of the composite reached the V-0 level of UL-94 fire rating with an ultimate oxygen index (LOI) of 26.4%. The average heat release rate (Av-HRR), peak heat release rate (PHRR), and total heat release rate (THR) decreased by 45.9, 56.5, and 32.6%, respectively. This shows that LGF/PBT/DOPO-HQ composite has good flame-retardant properties. Meanwhile, the flame-retardant mechanism of cohesive phase and gas-phase synergy during the combustion of flame retardants was analyzed by carbon layer morphology and dynamic thermal decomposition.